Femininity, Mathematics and Science, 1880–1914 - Jones, C. author. aut Link
IX, 264 p. 9 illus.
Keywords: Through the prism of gender, this text explores the contrasting cultures and practice of mathematics and science and asks how they impacted on women. Claire Jones assesses nineteenth-century ideas about women's intellect, femininity and masculinity, and assesses how these attitudes shaped women's experiences as students and practitioners.